Intra-domain traffic engineering with shortest path routing protocols - Altın, Ayşegül; Fortz, Bernard; Thorup, Mikkel; Ümit, Hakan (Annals of operations research, 2013)
Throughout the last decade, extensive deployment of popular intra-domain routing protocols such as open shortest path first (OSPF) and intermediate system–intermediate system (IS-IS), has drawn an ever increasing attention to internet traffic engineering. This paper reviews optimization techniques that have been deployed for managing intra-domain routing in networks operated with shortest path routing protocols, and the state-of-the-art research that has been carried out in this direction.